Challenges for Teaching Wireless Communications Standards at the Graduate Level - Laura Pierucci (MDPI AG, 2019)
Telecom operators and companies ask for graduates with a specific education on the standards of the Institute of Electrical and Electronic Engineers (IEEE) or the 3rd Generation Partnership Project (3GPP), and the University curricula must consider these needs. The standards are written in a technical form, in a language understandable only by experts, and the technical details and algorithms are not often outlined. Therefore, a new educational methodology must be applied because the teachers have to bridge the gap between the basic knowledge (and the poor technical language) of students and the technical specifics of the standards. The paper presents a structured methodology to provide innovative teaching of the wireless standards for the Engineering Master's degree, according to the Conceive, Design, Implement, and Operate (CDIO) initiative and project based learning. The methodology is organized in three learning phases to understand the standardization process and improve students' skills to implement standard compliant communications systems. This challenge can be only won with laboratory activities to assist students in understanding wireless standards and with hands-on experiences during the internship period at telecom operators with the vision of a close cooperation between universities and telecom operators. Only in this way can the students achieve a solid background in designing and developing prototypes compliant with wireless communications standards and working skills for their future professional engineering careers. The effectiveness of the adopted educational methodology to provide innovative learning of wireless standards is evaluated by questionnaires filled in online by students and by the achieved skills implemented as confirmed by telecom operators. In this vision, the paper provides decision support to leaders in educational organizations to teach wireless standards effectively.